Evaluation of the Maturity Level of Information Technology Security Systems Using KAMI Index Version 4.2 (Case Study: Islamic Boarding Schools in Yogyakarta Special Region Province) - Arromdoni, Bad’ul Hilmi; Nuruzzaman, Muhammad Taufiq; 'Uyun, Shofwatul; Sugiantoro, Bambang (IJID (International Journal on Informatics for Development), 2023)
The development of information technology worldwide has changed very rapidly. There has been a data theft on the information system belonging to one of the most prominent Islamic Boarding Schools in the Yogyakarta area. Thus, special attention is needed to evaluate information technology security using the Information Security Index version 4.2. The research methods include extracting information, literature study, data collection, data validation, data analysis, and recommendations. The evaluation results are at the basic framework fulfilment level with a value of 343; the electronic system category has a low status with a value of 15 and 5 improvements; the governance category,  the risk management category,  the framework category,  the asset management category, and the information security technology category, have a maturity level II status with 12, five, eight, four, and eight recommendations respectively, while the supplement category for third party security areas with a value of 60%, securing cloud infrastructure services 56% and protecting personal data 61% with 14 recommendations.